Geographical Names Study of Nagari, a Local Customary-Based Community Unit in Agam Regency, Indonesia - Sevicha, Dinda Putri; Cahyono, Ari (EDP Sciences, 2023)
Nagari names in Agam Regency are lacking historical record despite being a fundamental spatial information. Preliminary research has revealed inconsistencies in nagari name records, even in official government documents. This paper conducts an analysis of nagari names within Agam Regency, West Sumatra Province, Indonesia. Geographical names depict both the natural landscape and human activities, including their interaction with the environment 1, and Agam Regency spans from sea level to 2891 meters, featuring diverse landscapes, while the formation of nagari is deeply rooted in local customary law. This raises a question: what are nagari names in Agam Regency, and what do they signify?. Therefore, the objectives are: 1) establishing a digital nagari name database for Agam Regency, and 2) analysing geographical names based on linguistic and historical meanings. Primary methods used are interviews and literature studies. Approximately 52.44% of names are related to man-made features, human activities, and interactions, while others derive from natural features or a combination of both. Nagari names were found to be clustered around Bukittinggi and Lubuk Basung, historically significant regions. This study contributes to the preservation of nagari names in Agam Regency, and the digital database holds potential for further spatial analyses. © 2023 EDP Sciences. All rights reserved.